2007
DOI: 10.1016/j.neuron.2007.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Cold Sensitivity in TRPM8 Null Mice

Abstract: Thermosensation is an essential sensory function that is subserved by a variety of transducer molecules, including those from the Transient Receptor Potential (TRP) ion channel superfamily. One of its members, TRPM8 (CMR1), a ligand-gated, nonselective cation channel, is activated by both cold and chemical stimuli in vitro. However, its roles in cold thermosensation and pain in vivo have not been fully elucidated. Here, we show that sensory neurons derived from TRPM8 null mice lack detectable levels of TRPM8 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
657
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 670 publications
(696 citation statements)
references
References 33 publications
35
657
3
1
Order By: Relevance
“…It is now well established that the TRPM8 ion channel present in sensory afferents is an important transducer of cold [4][5][6]27 . We found that Trpm8 -/-12 mutant mice are incapable of perceiving mild cold and this lack of behavior is correlated with the loss of cold-evoked activity in cortical L2/3 neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is now well established that the TRPM8 ion channel present in sensory afferents is an important transducer of cold [4][5][6]27 . We found that Trpm8 -/-12 mutant mice are incapable of perceiving mild cold and this lack of behavior is correlated with the loss of cold-evoked activity in cortical L2/3 neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Transient receptor potential melastatin 8 (TRPM8) has been identified as an ion channel receptor protein that mediates cold transduction in sensory afferent neurons that innervate the skin 26,27 and is involved in cold avoidance behavior in mice [4][5][6]22 . Whole-cell patch clamp recordings from L2/3 cortical neurons in forepaw S1 in anaesthetized Trpm8 -/-and Trpm8 +/+ littermate control mice during cold thermal stimulation of the forepaw revealed that six of eight neurons in Trpm8 +/+ mice showed a subthreshold response to cooling.…”
Section: Cooling Perception Involves Trpm8mentioning
confidence: 99%
See 2 more Smart Citations
“…Small‐diameter primary afferents, C‐fiber and A‐delta, are believed to mediate abnormal temperature sensitivity following nerve injury or neurotoxicity in rats (Colburn et al. 2007; Leith et al. 2010; Xiao et al.…”
Section: Discussionmentioning
confidence: 99%